2002
DOI: 10.1046/j.1468-3148.2002.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive–Behavioural Treatment of Anger Intensity among Offenders with Intellectual Disabilities

Abstract: Background Aggressive behaviour has been identified as a significant problem amongst people with intellectual disabilities living in institutional settings. Anger is a key activator of aggressive behaviour, as well as being an important element of clinical distress related to adverse life experiences. There is some evidence for the value of cognitive-behavioural treatments for anger problems with people having intellectual disabilities. No controlled studies of anger treatment involving intellectually disabled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 25 publications
0
101
0
7
Order By: Relevance
“…169 However, there was no significant effect on challenging behaviour in the only previous controlled trials of anger interventions where this was evaluated. 16,46 To the best of our knowledge, this is the first controlled study to report improved selfmanagement of aggressive challenging behaviour by people with intellectual disabilities.…”
Section: Outcomes For Service Usersmentioning
confidence: 86%
See 1 more Smart Citation
“…169 However, there was no significant effect on challenging behaviour in the only previous controlled trials of anger interventions where this was evaluated. 16,46 To the best of our knowledge, this is the first controlled study to report improved selfmanagement of aggressive challenging behaviour by people with intellectual disabilities.…”
Section: Outcomes For Service Usersmentioning
confidence: 86%
“…The participants in these studies included people with mild intellectual disabilities as well as some more intellectually able people whose FSIQ was in the 'borderline' range. 16,46,47 In reviewing these studies, a number of methodological issues are apparent:…”
Section: Anger In People With Intellectual Disabilitiesmentioning
confidence: 99%
“…67 There is considerable interest in the use of different drug treatments, such as topiramate, 68 and also in psychological treatments in challenging behaviour, with some indications that anger management and cognitive behavioural approaches are effective, [69][70][71][72] and developments in these management strategies are likely to be accelerated as a result of our findings.…”
mentioning
confidence: 78%
“…Additional eligibility criteria were applied to exclude studies if data were included in a later study (Rose, West, & Clifford, 2000;Taylor et al, 2002), or if insufficient data were reported to perform the meta-analysis (Matson, 1981;Willner et al, 2005). Finally, the study by Silvestri (1977) was excluded because twenty-three out of thirty items of its primary outcome however, that only half the number of trials delivering individual therapy were identified compared to those delivering group therapy.…”
Section: Meta-analysesmentioning
confidence: 99%